Feeding fodder beet (Beta vulgaris L.) versus pasture reduces methane emissions and nitrogen excretion in sheep - Xuezhao Sun; David Pacheco; Long Cheng; Sarah Maclean; Dongwen Luo; Peter H. Janssen (Animal Feed Science and Technology, 2026)

Matching climate to biological scales - David H. Klinges; Martha M. Muñoz; Saúl F. Domínguez-Guerrero; Ilya M.D. Maclean; Michael R. Kearney; David K. Skelly (Trends in Ecology & Evolution, 2026)

Orphan Receptor GPRC5B Controls Adult Hippocampal Neurogenesis and Affects Retinoic Acid-Mediated Behaviors - Wenqi Fu; Rana Alabdali; Alireza Mousaei; Fernanda Daher; Nina Wettschureck; David M. MacLean; Manoela V. Fogaça; Cesare Orlandi (Molecular Neurobiology, 2026)

The effects of muscle temperature on the muscle blood flow-oxygen consumption relationship during single leg isokinetic exercise - Dominique D. Gagnon; Alexus McCue; Juha E. Peltonen; David Marsh; David MacLean; Olivier Serresse (Journal of Thermal Biology, 2025)

Effects of feeding forage rape or chicory in a grass silage and concentrate-based diet as supplementary crops to replace irrigated pasture on performance, rumen metabolism and microbiome - Juan P. Keim; Natalia Quezada; Sandra Salazar; Rubén G. Pulido; Paul Maclean; David Pacheco; Nikola Palevich; Silvana Bravo; Camila Muñoz; Einar Vargas-Bello-Pérez (Animal Feed Science and Technology, 2025)

Evaluation of a dairy-derived stillage fertilizer for greenhouse-cultivated pepper (Capsicum annuum L.) - Mina Nasr-Sharif; Jessica Gaudet; David Geros; Alexandre Poulain; Allyson M. MacLean (Journal of Water Process Engineering, 2025)

Functional assessments of short-term spatial memory in the Dog Aging Project identify strong associations with age that are not moderated by body mass - Stephanie H. Hargrave; Amber J. Keyser; Emma Kristal; Gene E. Alexander; Theadora A. Block; Emily E. Bray; Laura E. L. C. Douglas; Brenda S. Kennedy; Daniel E. L. Promislow; David A. Raichlen; Dog Aging Project Consortium; Evan L. MacLean (GeroScience, 2025)

Increased monetary equity and health wellbeing benefits for marginal urban socioeconomic groups from access to green space - Adam Loch; Stuart Sexton; John Maclean; Patrick O’Connor; David Adamson; Glen Scholz (Urban Forestry & Urban Greening, 2024)

Proximal microclimate: Moving beyond spatiotemporal resolution improves ecological predictions - David H. Klinges; J. Alex Baecher; Jonas J. Lembrechts; Ilya M. D. Maclean; Jonathan Lenoir; Caroline Greiser; Michael Ashcroft; Luke J. Evans; Michael R. Kearney; Juha Aalto; Isabel C. Barrio; Pieter De Frenne; et al. (Global Ecology and Biogeography, 2024)
Aim The scale of environmental data is often defined by their extent (spatial area, temporal duration) and resolution (grain size, temporal interval). Although describing climate data scale via these terms is appropriate for most meteorological applications, for ecology and biogeography, climate data of the same spatiotemporal resolution and extent may differ in their relevance to an organism. Here, we propose that climate proximity, or how well climate data represent the actual conditions that an organism is exposed to, is more important for ecological realism than the spatiotemporal resolution of the climate data. Location Temperature comparison in nine countries across four continents; ecological case studies in Alberta (Canada), Sabah (Malaysia) and North Carolina/Tennessee (USA). Time Period 1960–2018. Major Taxa Studied Case studies with flies, mosquitoes and salamanders, but concepts relevant to all life on earth. Methods We compare the accuracy of two macroclimate data sources (ERA5 and WorldClim) and a novel microclimate model ( microclimf ) in predicting soil temperatures. We then use ERA5, WorldClim and microclimf to drive ecological models in three case studies: temporal (fly phenology), spatial (mosquito thermal suitability) and spatiotemporal (salamander range shifts) ecological responses. Results For predicting soil temperatures, microclimf had 24.9% and 16.4% lower absolute bias than ERA5 and WorldClim respectively. Across the case studies, we find that increasing proximity (from macroclimate to microclimate) yields a 247% improvement in performance of ecological models on average, compared to 18% and 9% improvements from increasing spatial resolution 20‐fold, and temporal resolution 30‐fold respectively. Main Conclusions We propose that increasing climate proximity, even if at the sacrifice of finer climate spatiotemporal resolution, may improve ecological predictions. We emphasize biophysically informed approaches, rather than generic formulations, when quantifying ecoclimatic relationships. Redefining the scale of climate through the lens of the organism itself helps reveal mechanisms underlying how climate shapes ecological systems.

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

Microclimate, an important part of ecology and biogeography - Julia Kemppinen; Jonas J. Lembrechts; Koenraad Van Meerbeek; Jofre Carnicer; Nathalie Isabelle Chardon; Paul Kardol; Jonathan Lenoir; Daijun Liu; Ilya Maclean; Jan Pergl; Patrick Saccone; Rebecca A. Senior; et al. (Global Ecology and Biogeography, 2024)
Brief introduction: What are microclimates and why are they important? Microclimate science has developed into a global discipline. Microclimate science is increasingly used to understand and mitigate climate and biodiversity shifts. Here, we provide an overview of the current status of microclimate ecology and biogeography in terrestrial ecosystems, and where this field is heading next. Microclimate investigations in ecology and biogeography We highlight the latest research on interactions between microclimates and organisms, including how microclimates influence individuals, and through them populations, communities and entire ecosystems and their processes. We also briefly discuss recent research on how organisms shape microclimates from the tropics to the poles. Microclimate applications in ecosystem management Microclimates are also important in ecosystem management under climate change. We showcase new research in microclimate management with examples from biodiversity conservation, forestry and urban ecology. We discuss the importance of microrefugia in conservation and how to promote microclimate heterogeneity. Methods for microclimate science We showcase the recent advances in data acquisition, such as novel field sensors and remote sensing methods. We discuss microclimate modelling, mapping and data processing, including accessibility of modelling tools, advantages of mechanistic and statistical modelling and solutions for computational challenges that have pushed the state‐of‐the‐art of the field. What's next? We identify major knowledge gaps that need to be filled for further advancing microclimate investigations, applications and methods. These gaps include spatiotemporal scaling of microclimate data, mismatches between macroclimate and microclimate in predicting responses of organisms to climate change, and the need for more evidence on the outcomes of microclimate management.

Opposing genetic patterns of range shifting temperate and tropical gastropods in an area undergoing tropicalisation - Karolina M. Zarzyczny; Michael E. Hellberg; Elena B. Lugli; Moira MacLean; David A. Paz‐García; Marc Rius; Ethan G. Ross; Erick X. Treviño Balandra; James Vanstone; Suzanne T. Williams; Phillip B. Fenberg (Journal of Biogeography, 2024)
Aim The poleward range expansion of tropical species, and range contraction of temperate species (known as tropicalisation) has mainly been studied from an ecological perspective, with little research on its genetic consequences. Here, we used distributional and genetic data to document the consequences of tropicalisation in rocky shore gastropods and assess more broadly the future implications of tropicalisation on phylogeographic patterns. Location Nineteen sampling sites along >3000 km of the eastern Pacific rocky intertidal zone, from the tip of the Baja California Peninsula to southern California. Taxon Temperate gastropods: Lottia conus , L. strigatella , Fissurella volcano and Tegula gallina. Tropical gastropods: Fissurella rubropicta , Nerita funiculata and N. scabricosta. Methods We determine historical and modern distributions of tropical and temperate species by combining historical records with current field surveys. Using a section of the cytochrome oxidase subunit I gene, we utilised comparative phylogeography, analysis of molecular variance, F ST pairwise comparison, mismatch distributions of haplotype differences and neutrality tests to detect genetic signatures of tropicalisation and to better understand its consequences. Results We identified range contractions in two temperate species and range expansion in all three tropical species. We detected genetic signatures of range expansion in the tropical species through unimodal distributions of pairwise haplotype differences and strongly negative values for the Fu and Li D and F * statistics. We found population subdivision and phylogeographic breaks in three temperate species, although the geographic location of the breaks differed among species. Main Conclusions Genetic signatures and field surveys indicate recent range expansions in tropical species, supporting tropicalisation along the studied coastline. Conversely, we found phylogeographic breaks in temperate species, suggesting that tropicalisation may cause genetic erosion of evolutionary distinct lineages with range‐contraction. The different locations of the phylogeographic breaks among temperate species suggests that some barriers are species specific.

Predator‐induced defences under tropicalisation: A biogeographic approach - Phillip B. Fenberg; Rodrigo Beas‐Luna; Boris Igić; Moira A. MacLean; David A. Paz‐García; Peter T. Raimondi; Jacqueline L. Sones; Karolina M. Zarzyczny; Eric Sanford (Journal of Biogeography, 2023)
Aim The biogeography of predator‐induced defences is an understudied area of predator–prey dynamics. Range overlap with predators that induce the response and local demographics (e.g., prey abundances) are likely to be important factors for determining the biogeographic distribution of induced defences within species. However, with climate warming, range‐expanding warm‐water predators are increasingly preying upon temperate species. This is a consequence of a wider phenomenon known as tropicalisation. We aim to determine: (i) if individuals of a temperate barnacle with induced defences (‘bent morphs’) are primarily present where they co‐occur with range‐expanding warm‐water predators (muricid snails) and, (ii) if bent morphs are size‐structured within populations. Location North‐eastern Pacific rocky intertidal zone (~26–40° N). Taxon Tetraclita rubescens (Nilsson‐Cantell, 1931), Balanomorpha. Methods We use photoquadrats from sites across the range of T. rubescens to determine the biogeographic distribution of populations with bent morphs and to assess size‐structure. We use a combination of field surveys, literature, and museum occurrences to assess range overlap between cool and warm‐water predators of T. rubescens and their association with populations with bent morphs and abundance patterns of T. rubescens . Results Bent morphs are commonly found within the equatorward portion of the species' range (where abundances are highest), in populations overlapping with range‐expanding warm‐water predators. Bent morphs primarily occur within the smaller size classes. Main conclusions To be partly resilient to the effects of tropicalisation, temperate prey must acclimatise/adapt to altered predator–prey dynamics. Predator‐induced defences are one way to do this. We show that bent morphs within a temperate prey species ( T. rubescens ) are largely restricted to populations that overlap with large‐bodied and range‐expanding warm‐water predators. This is evidence for the partial resilience of T. rubescens to tropicalisation and provides the rationale for further exploration of the eco‐evolutionary consequences of tropicalisation in this study system and others.

Forester and Logger Response to Emerald Ash Borer in Massachusetts and Vermont: A Secondary Disturbance - Marla Markowski-Lindsay; Paul Catanzaro; Amanda Robillard; Brett J Butler; David A Orwig; Anthony W D’Amato; Jonathan R Thompson; Danelle M Laflower; Meghan Graham MacLean; Malcolm Itter (Journal of Forestry, 2023)
Forester and logger responses to the invasive emerald ash borer (EAB) could substantially affect regions across the United States. We analyzed forester and logger responses to EAB in Massachusetts and Vermont, exploring characteristics associated with purposeful targeting of substantial ash properties; managing forests differently because of EAB; and regeneration goals. One-third of respondents increased timber sales on ash properties, motivated by ecological, not economic, impacts of EAB. Nearly 60% said EAB changed their management activity in stands with ash; changes influenced by the ecological impact of EAB and not economic factors. Those influenced by EAB’s ecological impact to choose properties with substantial ash were more likely to have increased harvest area size, sawtimber removal, and harvest intensity. Loggers were more likely than foresters to remove small-diameter ash and low-grade trees. Both rated regenerating economically valuable species well adapted to the site as their highest essential priority.

Historical pesticide applications for the treatment of eastern spruce budworm infestations in New Brunswick - Shane Heartz; David A. MacLean; Rob C. Johns; Drew Carleton; Luke Amos‐Binks; Quinn Anderson; Yue Yu; Andrew D. Lewis; Dan Lavigne; Joseph B. Burant; Christopher B. Edge (Ecology, 2023)
Pesticides have been used in Canada since 1945 as part of large‐scale aerial spray applications to control insect pests on forested lands. Some of the pesticides used historically were efficacious, nonselective, persistent, and have led to serious impacts on the environment. A well known, and extensively documented example is the large‐scale aerial spray programs in New Brunswick, Canada. From 1952 to 1993, 97% of the 6.2 million ha of the forested lands of New Brunswick were treated with at least one application of one insecticide, the majority of which were applied to control outbreaks of eastern spruce budworm ( Choristoneura fumiferana ). The most well known insecticide was dichlorodiphenyltrichloroethane (DDT), applied from 1952 to 1968, which still persists in treated soils and adjacent water bodies, and caused the individual and cumulative ecosystem effects that can still be measured today. The insecticides that replaced DDT were nonpersistent and unlikely to be found today. However, during the years of application some of the insecticides were likely to have impacted local ecosystems to some degree. To aid future studies on the efficacy and environmental impact of these insecticides we created a digital spatial data set of known pesticide application in New Brunswick forestry from 1952 to 1993. The data set includes active ingredient, formulation, application rate, tank mix, aircraft type, and other ancillary information. The current version of the data is available on the New Brunswick Department of Natural Resources and Energy Development, GIS Open Data Page and in the supplemental material. Use of the data set for academic and educational purposes is encouraged, provided that both this data paper and the data source are properly cited; the Government of New Brunswick should be acknowledged as the data source (Open Government License http://www.snb.ca/e/2000/data-E.html ).

Associations between physical activity and cognitive dysfunction in older companion dogs: results from the Dog Aging Project - Emily E. Bray; David A. Raichlen; Kiersten K. Forsyth; Daniel E. L. Promislow; Gene E. Alexander; Evan L. MacLean; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; et al. (GeroScience, 2023)

Modeling the distribution of Acadian vascular rare plant species under future climate scenarios - Jiban Chandra Deb; Shane Furze; David A. MacLean (Plant Ecology, 2023)

Correlations between spatial sampling biases and environmental niches affect species distribution models - David J. Baker; Ilya M. D. Maclean; Martin Goodall; Kevin J. Gaston (Global Ecology and Biogeography, 2022)
Aim Spatial sampling biases in biodiversity data arise because of complex interactions between geography, species characteristics and human behaviour, including preferences for or against particular species or habitats; biases are therefore not necessarily independent of the environmental niches of species. We evaluate when correlations between spatial sampling biases and environmental niches are likely to affect species distribution models (SDMs) developed both with and without attempts to correct these biases. Innovation A virtual species and virtual ecologist framework was used to simulate biodiversity data with either no spatial sampling bias or biases that were correlated (positively or negatively) with one of the environmental variables used to define the environmental niches of the species. The environmental variables used to define the species niche were simulated with spatial autocorrelation operating at multiple spatial scales. Virtual samples were then used to model species distributions, with models evaluated based on their ability to rank the suitability of sites correctly. Main conclusions Correlations between spatial sampling bias and environmental niches frequently reduced the rank correlation of model predictions, but the relative importance of these effects varied with species type (greater decline in rank correlation as the environmental niche broadens) and data type (models built using detection/non‐detection data were less affected than those using detection‐only data). Bias‐correction effectiveness varied depending on the structure of the spatial bias but was also highly variable across methods and dependent on data type. The implications of these results are that spatial sampling bias is a greater concern for SDMs where: (1) the distribution of effort is non‐random with respect to an environmental gradient thought to be correlated with a species’ distribution; (2) the species being modelled has a broad environmental niche; and (3) the data for modelling contain only information on detections (i.e., presence only).

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Efficiently Simulating an Endograft Deployment: A Methodology for Detailed CFD Analyses - Faidon Kyriakou; Craig Maclean; William Dempster; David Nash (Annals of Biomedical Engineering, 2020)
Numerical models of endografts for the simulation of endovascular aneurysm repair are increasingly important in the improvement of device designs and patient outcomes. Nevertheless, current finite element analysis (FEA) models of complete endograft devices come at a high computational cost, requiring days of runtime, therefore restricting their applicability. In the current study, an efficient FEA model of the Anaconda™ endograft (Terumo Aortic, UK) was developed, able to yield results in just over 4 h, an order of magnitude less than similar models found in the literature. The model was used to replicate a physical device that was deployed in a 3D printed aorta and comparison of the two shapes illustrated a less than 5 mm placement error of the model in the regions of interest, consistent with other more computationally intensive models in the literature. Furthermore, the final goal of the study was to utilize the deployed fabric model in a hemodynamic analysis that would incorporate realistic fabric folds, a feature that is almost always omitted in similar simulations. By successfully exporting the deployed graft geometry into a flow analysis, it was illustrated that the inclusion of fabric wrinkles enabled clinically significant flow patterns such as flow stagnation and recirculation to be detected, paving the way for this modelling methodology to be used in future for stent design optimisation.

Use of QSPR Modeling to Characterize In Vitro Binding of Drugs to a Gut-Restricted Polymer - Christine Taylor Brew; James F. Blake; Anita Mistry; Fengling Liu; Diana Carreno; Deidre Madsen; YongQi Mu; Martha Mayo; Wilhelm Stahl; David Matthews; Derek Maclean; Steve Harrison (Pharmaceutical Research, 2018)

Invasion by Rhododendron ponticum depletes the native seed bank with long-term impacts after its removal - Janet E. Maclean; Ruth J. Mitchell; David F. R. P. Burslem; David Genney; Jeanette Hall; Robin J. Pakeman (Biological Invasions, 2018)

Needle longevity of balsam fir is increased by defoliation by spruce budworm - Olivia Doran; David A. MacLean; John A. Kershaw (Trees, 2017)

A reply to ‘A meta-database of Holocene sediment cores for England: missing data’ (Tooley 2015) - Andrew J. Suggitt; Richard T. Jones; Chris J. Caseldine; Brian Huntley; John R. Stewart; Stephen J. Brooks; Eleanor Brown; David Fletcher; Phillipa K. Gillingham; Jonathan Larwood; Nicholas A. Macgregor; Barbara Silva; et al. (Vegetation History and Archaeobotany, 2015)

A meta-database of Holocene sediment cores for England - Andrew J. Suggitt; Richard T. Jones; Chris J. Caseldine; Brian Huntley; John R. Stewart; Stephen J. Brooks; Eleanor Brown; David Fletcher; Phillipa K. Gillingham; Jonathan Larwood; Nicholas A. Macgregor; Barbara Silva; et al. (Vegetation History and Archaeobotany, 2015)

Estimation of potential impacts of climate change on growth and yield of temperate tree species - M. Irfan Ashraf; Charles P.-A. Bourque; David A. MacLean; Thom Erdle; Fan-Rui Meng (Mitigation and Adaptation Strategies for Global Change, 2015)

Resolving issues with environmental impact assessment of marine renewable energy installations - Ilya M. D. Maclean; Richard Inger; David Benson; Cormac G. Booth; Clare B. Embling; W. James Grecian; Johanna J. Heymans; Kate E. Plummer; Michael Shackshaft; Carol E. Sparling; Ben Wilson; Lucy J. Wright; et al. (Frontiers in Marine Science, 2014)

Storm-induced shifts in optimal nesting sites: a potential effect of climate change - David N. Bonter; Sarah A. MacLean; Shailee S. Shah; Michelle C. Moglia (Journal of Ornithology, 2014)

Applying a Spruce Budworm Decision Support System to Maine: Projecting Spruce-Fir Volume Impacts under Alternative Management and Outbreak Scenarios - Chris R. Hennigar; Jeremy S. Wilson; David A. MacLean; Robert G. Wagner (Journal of Forestry, 2011)
Spruce budworm (SBW) infestations and defoliation in forests of eastern North America (e.g., 1910s, 1940s, and 1970‐1980s) have had significant negative impacts on growth and survival of spruce and fir. The Spruce Budworm Decision Support System (SBWDSS), originally developed by the Canadian Forest Service, can assist with SBW management planning by estimating the marginal timber supply (in cubic meters per hectare) benefits of protecting stands against budworm defoliation. We applied the SBWDSS to Maine and for two private forests (≈10,000-ha townships) to assess potential spruce-fir losses. Application of the approach across diverse forest types and data sets revealed dramatic differences in potential volume impacts between the two townships. The statewide analysis suggested that over 4 million ha of Maine's forest are vulnerable to the budworm. Projections of moderate and severe intensity outbreaks reduced statewide spruce-fir inventories by 20‐30% over the next 10 years.

Future Spruce Budworm Outbreak May Create a Carbon Source in Eastern Canadian Forests - Caren C. Dymond; Eric T. Neilson; Graham Stinson; Kevin Porter; David A. MacLean; David R. Gray; Michel Campagna; Werner A. Kurz (Ecosystems, 2010)

Legacy of Insect Defoliators: Increased Wind-Related Mortality Two Decades After a Spruce Budworm Outbreak - Sarah L. Taylor; David A. MacLean (Forest Science, 2009)
Effects of spruce budworm (Choristoneura fumiferana Clem.) outbreaks on growth and survival of balsam fir (Abies balsamea [L.] Mill.) and spruce (Picea spp.) are well documented, but few studies extend beyond 10 years after defoliation ceased. We used inventory data from 106 permanent sample plots in >50-year-old balsam fir stands in northern New Brunswick, Canada, to determine legacy effects of the 1969–1993 budworm outbreak on stand development up to 29 years after defoliation ceased. Defoliation data were from annual aerial surveys from 1945 to 1993 and plot ground sampling from 1985 to 1993. Plots were stratified into net stand volume development categories (decreasing, stable, and increasing 1985–2005 stemwood volume) and related to outbreak phases (outbreak, direct 1–10 years after defoliation ceased, and legacy >10 years), outbreak severity (1–4 [low], 5–8 [medium], and 9–12 [high] years of defoliation), and stand age (mature and overmature). Stand age was an important factor influencing outbreak severity (e.g., r2 = 0.383, P < 0.01). Trend and rate of volume development over time were related to past outbreak severity and increased rate of postoutbreak wind-related mortality, which peaked at 11 m3/ha/yr 11–15 years after defoliation ceased. Results indicate that aging postoutbreak stands are more vulnerable to wind disturbance events, effecting rapid stand decline.

The Severity of Budworm-Caused Growth Reductions in Balsam Fir/Spruce Stands Varies with the Hardwood Content of Surrounding Forest Landscapes - Elizabeth M. Campbell; David A. MacLean; Yves Bergeron (Forest Science, 2008)
Tree-ring data collected from balsam fir (Abies balsamea [L.] Mill.) in 31 spruce (Picea spp.)/fir-dominated stands in northern New Brunswick were used to evaluate how radial growth reductions during the last spruce budworm (Choristoneura fumiferana Clem.) outbreak (1972–1992) varied according to the hardwood content of surrounding forest landscapes, insecticide spray history and elevation. Stepwise regression analysis was used to build 12 models describing relationships between mean percent growth reduction (i.e., deviation from mean tree growth averaged over the lifespan of all trees in a stand) and the explanatory variables for years when >80% of stands had growth reductions (1976–1978, 1982–1984, 1990, 1991, and 1994) and for three growth reduction periods (1972–1980, 1981–1985, and 1986–1993). The hardwood content of surrounding forest landscapes entered into all significant regression models (P < 0.05), explaining 12–41% of the variance in budworm-caused growth reductions. Differences in growth reductions among stands were greatest during the initial years of the budworm outbreak (1972–1980), particularly in 1976 when mean reductions were 40% in stands with <50% hardwood and content and 20% in stands in which surrounding hardwood content was >50%. Relationships between variation in growth reductions among stands and elevation or insecticide spray history were weak and less consistent than with landscape hardwood content. Our findings suggest that increasing the hardwood content of forest landscapes could help to reduce the impact of outbreaks on timber supplies.

Differences in Spruce Budworm Defoliation among Balsam Fir and White, Red, and Black Spruce - Chris R. Hennigar; David A. MacLean; Dan T. Quiring; John A. Kershaw (Forest Science, 2008)
Spruce budworm (Choristoneura fumiferana Clem.) outbreaks severely reduce growth and survival of balsam fir (Abies balsamea [L.] Mill.) and spruce (Picea spp. A. Dietr.) over much of eastern North America, resulting in major reductions in yield and disruption of harvest schedules. This is the first study to rigorously quantify defoliation differences among all four spruce budworm host tree species at a stand level. An extensive permanent sample plot data set, with more than 27,000 tree and 1,117 stand measurements from 1984 to 1992 in New Brunswick, Canada, revealed a clear and consistent hierarchy of host species defoliation susceptibility. Regardless of defoliation severity and other stand variables tested, white (Picea glauca [Moench] Voss), red (Picea rubens Sarg.), and black spruce (Picea mariana [Mill.] B.S.P.) had approximately 72, 41, and 28% as much defoliation as balsam fir, respectively. Balsam fir defoliation was a highly significant predictor of white, red, and black spruce defoliation. Of the variation in defoliation of red-black spruce hybrids, 34% was explained by balsam fir defoliation and an interaction with spruce hybrid index. This is the first model to quantify hybrid red-black spruce defoliation across a full range of severities. Quantitative models of stand-level defoliation differences among host species will improve spruce budworm stand impact forecasts and decision support prioritization of bioinsecticide or salvage operations and provide information to calibrate population-defoliation models for host species in mixed species stand types.

Venous but not skeletal muscle interstitial nitric oxide is increased during hypobaric hypoxia - Urs A. Leuenberger; Douglas Johnson; Joseph Loomis; Kristen S. Gray; David A. MacLean (European Journal of Applied Physiology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Mitochondrial DNA Clocks and the Phylogeny of Danaus Butterflies - Gugs Lushai; David A. S. Smith; Dave Goulson; John A. Allen; Norman Maclean (International Journal of Tropical Insect Science, 2003)

The Influence of Forest and Stand Conditions on Spruce Budworm Defoliation in New Brunswick, Canada - Wayne E. MacKinnon; David A. MacLean (Forest Science, 2003)
The species composition of stands and surrounding forest have been suggested as important factors influencing the amount of spruce budworm (Choristoneura fumiferana [Clem.]) defoliation and, consequently, budworm-induced growth loss and mortality. We measured spruce budworm defoliation from 1989–1993 in 40 spruce (Picea sp.) and balsam fir (Abies balsamea [L.] Mill.) stands in north-central New Brunswick, Canada, and evaluated the influence of surrounding forest type (softwood, mixedwood), species group (balsam fir, spruce), and site quality (wet/nutrient poor, moist/nutrient rich) on defoliation. Surrounding forest type had a significant effect on the amount of defoliation in white spruce (Picea glauca [Moench] Voss) stands; stands in softwood forests sustained 11% more (P = 0.0485) defoliation than those in mixedwood. There was evidence that hardwood species have to be within, rather than surrounding, a spruce-fir stand to significantly influence defoliation. Site quality had a significant effect (P = 0.0039) on balsam fir defoliation, with stands on moist/rich sites sustaining 19% more defoliation than those on wet/poor sites. In softwood forest, white spruce stands sustained an average of 16% more defoliation than red-black spruce (Picea rubens Sarg.-Picea mariana [Mill.] B.S.P.) stands.

Monitoring the in Vivo Delivery of Proteins from Carbomer Hydrogels by X-Ray Fluorescence - Donald S. MacLean-McDavitt; J. David Robertson; Michael Jay (Pharmaceutical Research, 2003)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Gene delivery to rat enteric neurons using herpes simplex virus-based vectors - M. Keith Howard; Robert S. Coffin; Alistair R. Maclean; S. Moira Brown; Doreen Bailey; Patricia N. Anderson; Geoffrey Burnstock; David S. Latchman (Journal of Molecular Neuroscience, 1997)